Analysis The Role of Mathematics As a Means of Deductive Thinking - Adhadini, Denanda Anggun Alfentin; Maisaroh, Siti; Mahardika, I Ketut; Mahmudi, Kendid; Wahid, Ahmad v; Lailiyah, Shofiyatul (Peneliti.net, 2024)
Mathematics, with its unique symbolic language and logical structure, has long been recognized as an effective tool for training the mind. This studyaims to delve deeper into the specific role of mathematics in developing deductive reasoning skills. Through a theoretical review and empirical analysis, this study identifies how mathematical concepts such as proofs, theorems, and problem-solving contribute to the formation of systematic and rational thinking patterns. The results of the study show that effective mathematics learning can provide a strong foundation for improving individuals' ability to think critically and solve complex problems